PENGEMBANGAN JAWA BARAT SEBAGAI PROVINSI JASA - Ria Satyarini (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Jawa Barat as the next province after DKI Jakarta has many strategic roles. Jawa Barat has a vision to be the most advance province in 2012, according to the vision Jawa Barat has to achieve that vision and reach the opportunity. There are so much to do and big challenges that Jawa Barat has to deal with. But the important things is how the government recognize classification of services and knows the challenge they face.